Kedudukan Hukum Perawat Bedah Pasca Pembedahan dalam Sengketa Medis di Rumah Sakit - Riyanto, Ontran Sumantri; Panggabean, Hetty W.A.; Kurniawan, Erik Adik Putra Bambang; Hitauruk, Monika (Fakultas Syariah INSURI Ponorogo, 2022)
Surgery is an effort to treat or help to treat a patient's disease. The increasing demand for health care is to increase, whether it is expected that a nurse improves her knowledge and skills, such as a surgical nurse specialist. This research uses normative juridical research methods, using secondary data sources including legislation, books, journals, court decisions, and other literature. The result of the study is that the surgical nurse while performing his duties both in the surgical room, before surgery, during surgery and after surgery must be based on SOPs and mandates from doctors made in writing. That way a surgical nurse if working is in accordance with the procedures and directions of the doctor, the surgical nurse cannot be sanctioned in the event of a medical dispute because his responsibility rests with the surgeon.